Characterization of Si3N4/SiC nanocomposite by Raman scattering and XPS - Cho, WS; Oh, YS; Kim, CS; Osada, M; Kakihana, M; Lim, DS; Cheong, DS (ELSEVIER SCIENCE SA, 1999)
We have synthesized Si3N4/SiC nanocomposites using a commercial polymer. The formed Si3N4/SiC nanocomposites have been studied using Raman scattering and X-ray photoelectron spectroscopy (WS). The Raman scattering measurements showed that the formation of SiC started at 1200 degrees C and that the main phase was 3C-SiC, The XPS results suggested that the SiC nanoparticles were formed by a chemical reaction of Si provided from Si3N4 with free carbon obtained by pyrolysis of polymer. The XPS results also indicated that residual carbon reacted with N-2 to form CNx, which remained as an impurity phase in the final product. (C) 1999 Elsevier Science S.A. All rights reserved.
Keywords: SILICON-CARBIDE; FILMS; SPECTROSCOPY; FABRICATION; TEMPERATURE; SURFACES